An appraisal for the petroleum source rocks on oil seep and rock samples of the Tertiary Seblat and Lemau Formations, Bengkulu Basin - Panggabean, Hermes; Heryanto, R. (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no1.20095The Tertiary Bengkulu Basin is known as a typical fore-arc basin, situated in southwest Sumatera. The basin initiated during Eocene-Oligocene times, accumulates the Lahat equivalent formation. The formation is is unconformably overlain by the Oligocene-Miocene Hulusimpang Formation consisting of volcanic rocks. It is then succeeded by siliciclastics and minor carbonates of the Early-Middle Miocene of Seblat Formation. Unconformably overlying the Seblat is siliciclastics of the Middle-Late Miocene Lemau Formation, then overlain by the Late Mio-Pliocene Simpangaur Formation. The basin succession is terminated by the sequence of volcanic rocks named as the Bintunan or Ranau Formation. Geochemistry analyses (i.e. TOC, Rock-Eval and Gas Chromatography-Mass Spectrometry) conducted on selected outcrop and sub-crop samples, and one oil seep sample collected during field work, have given an appraisal to identify the nature of petroleum source rocks within the basin. The result of organic geochemistry and also organic petrology analyses indicates that potential source rocks may occurred in the stratigraphic succession of the basin. The Lahat equivalent formation, Seblat, and Lemau Formations may play an important role to generate oil within the Bengkulu Basin. Â